The status of forest elephants in the south east of the Republic of Cameroon - Ekobo, Atanga (Pachyderm, 1993)
Reviews results from the recent transect survey covering three southeastern Cameroon areas, Lake Lobeke, Mongokele and Boumba-bek where based on dung density counts estimated elephant population for the areas were 11,225, 3,723 and 3,215 respectively. The study suggests that in spite of extensive logging and poaching activity in the region the elephant populations in the three survey areas do not appear to be in immediate jeopardy.